Improvement of polytrauma management‐quality inspection of a newly introduced course concept. Issue 6 (17th September 2017) - Gräff, Ingo; Ghamari, Shahab; Schacher, Sylvia; Glien, Procula; Fimmers, Rolf; Baehner, Torsten; Kim, Se‐Chan
Abstract: Rationale, aims, and objectives: A systematic literature search for training course concepts for care of severely injured and severely ill patients respecting improvement of process and outcome yielded little data. For several years, the University Hospital of Bonn has hosted a shock‐room management course which, on the one hand, communicates human factor aspects and, on the other hand, pursues interdisciplinary and interprofessional team training. The Bonn shock‐room management course (BSM‐course®) differs from other courses in both format and principles. The aim of this study was to evaluate the quality of the structure of the course based on course evaluations of participants and its impact on the quality of the process and results for polytrauma care. Methods: Single‐center retrospective evaluation study (2011 to 2014). It was based on data from simulator training and records from the German Trauma Registry (DGU)®. Results: Subjective evaluation of participants ( n  = 188) of the structure quality of Bonn's shock‐room management course was overall positive. Objective measures of course participant performance also improved during simulation training ( P  = 0.012). An increasing number of trained employees also had a positive influence in reducing process time for shock‐room care. Further, the course likewise had a positive impact on documentation quality (degree of completion), with regard to 4 relevant predictive parameters. Early mortality during the first 24 hours remained constant at 6.0‐6.5% between 2011 and 2013, yet it decreased to 3.1% in 2014. Conclusion: The BSM‐course® represents a symbiosis of horizontal team approach of trauma care and human factor training. The course format is able to ensure interdisciplinary and interprofessional team training with a high degree of efficiency. Furthermore, the presented work shows that a modern course concept can improve the quality of trauma care.